The Anxiety Level and Premature Rupture of Membrane Incidence during COVID-19 Pandemic - Nugraha, Renasheva Alifia; Bachnas, Muhammad Adrianes; Yuliadi, Istar (Indonesian Journal of Obstetrics and Gynecology, 2023)
Abstract Objective: To determine the association between anxiety level and premature rupture of membrane incidence during COVID-19 pandemic. Methods: This study was a case-control study. The subjects of this study were patients giving birth at RSUD Dr. Moewardi Surakarta Hospital and UNS Sukoharjo Hospital in June - October 2021. Sampling was done by the purposive sampling technique on 70 samples. Data were analyzed using the chi-square test and logistic regression test. Results: Characteristic data of the study samples found that most of the study samples was severe anxiety (40%). There was a significant association between the level of anxiety with PROM incident (p = 0.00), and pregnant women with severe anxiety had a risk of PROM of 3.761 times compared to pregnant women who were not anxious (OR=3.761). In multivariate analysis, it was found that the most influential variable on the incidence of premature rupture of membranes was the level of anxiety (p=0.001) compared to parity (p=0.155), employment status (0.193), and education level (0.576). Conclusion: There was a significant association between anxiety level and premature rupture of membranes incidence during the COVID-19 pandemic, and there was an increased risk of premature rupture of membranes in pregnant women with severe anxiety levels during the COVID-19 pandemic. Keywords: anxiety level; premature rupture of membrane; COVID-19 pandemic.